Evaluación del impacto ecológico de la tala selectiva en la regeneración natural del bosque tropical de montaña de la Estación Cietífica San Francisco - Chalco Torres, Maricela del Rocío (2013)
The present research project reinforces the knowledge about diversity, dynamic, floristic composition and the answer of the tropical forest of the mountain before the natural and anthropic perturbations. The objective of the research is to contribute to the conservation of the tropical mountain forests, through the generation of information, which serves as a basis to make decisions about the sustainable management of these types of ecosystems. The research was done in the San Francisco Scientific Station, in the watershed Q2 (reference forest) and Q5 (intervened forest), where 51 permanent parcels of land with measurements of 12 m x 12 m, distributed as follows: 19 in the watershed Q2 and 32 in the watershed Q5 (16 in the clear area of the forest and 16 in the area of covered forest). The specimens with an altitude greater than 5cm and with diameter at the height of the chest (DAP) less than 5 cm were sampled. The variables sampled were: diameter at the height of base (DAB), height, quality of the plant and recruitment and mortality With the data gathered, it was determined that the floristic composition and the ecological parameters like: abundance, density and frequency. Also to compare the dynamics of natural regeneration between the area intervened and the area of reference, the following parameters were determined: the annual recruitment and mortality rate, the periodic increase of the height and basal diameter, state of the plant, the Shannon index, index of Evenness, Sorensen index of similitude, and finally to determine the impact provoked by the natural regeneration, the threshold of the change of the ecological parameters of the richness and abundance of the species was determined. With the results obtained, it was evidenced that the natural and anthropic perturbations modify the floristic composition of these types of forests. In what respects to the annual periodic growth of the floristic composition in DAB and height, it was found that there doesn’t exist significant differences between the increase in the reference forest and the intervened forest, the median of growth is the same in both cases. In what respects to alpha diversity, the Shannon index of diversity shows that the area intervened and the area of reference are diverse, but the Sorensen index of similitude indicates that the two areas are moderately similar, that is that there is the presence of species that show preferences to certain conditions like the increase of light provoked by forestry intervention. In what respects to the mortality rate, the area with the greatest percentage is the area intervened (11.62% clear forest and 10.9% covered forest); the contrary is evidenced in the recruitment rate since the reference forest presents the greater rate of (10.76%). The threshold of change indicates that as the years pass, the intervened forest gets closer to the conditions presented by the forest of reference, in what respects to richness and abundance of species, that is the ecosystem is recuperating the conditions presented before the intervention in underwent.